STRATEGIC PLANNING FOR THE DEVELOPMENT OF PREFABRICATED HOUSE CONSTRUCTION INDUSTRY IN INDONESIA - Muhammad Rizal; Andi Sani Silwanah; Aldo Valentino Benjamin Puturuhu; Rafiandi Normansyah; Cica Permatasari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
The prefabricated house construction industry in Indonesia has enormous potential, driven by the high demand for housing, which reached 9.9 million, and supportive government policies, but it is still hit by multidimensional challenges that require comprehensive strategic planning. Thus, this study aims to map strategic planning to develop the prefabricated house construction industry in Indonesia. The research questions of this study are: (1) What are the factors that affect the development of the prefabricated house construction industry in Indonesia? (2) What strategic planning does Indonesia implement to develop this industry? This research was compiled by uncovering the growth of the prefabricated house construction industry and its situation in Indonesia, and adopting secondary data analysis to collect data. The results of the study by integrating the Diamond Porter Model and SWOT/TOWSanalysis revealed that the success of industrial development depends on a synergistic multi-stakeholder approach involving integrated policy support, technology adoption, supply chain consolidation, and comprehensive market education to transform Indonesia's housing sector towards greater efficiency, scalability, and sustainability.